2004
DOI: 10.1518/hfes.46.2.244.37337
|View full text |Cite
|
Sign up to set email alerts
|

Grip Force Vectors for Varying Handle Diameters and Hand Sizes

Abstract: Grip force was measured along two orthogonal axes and vector summed. Sixty-one participants recruited from a manufacturing facility (29 men and 32 women) grasped instrumented cylinders (2.54, 3.81, 5.08, 6.35, and 7.62 cm diameter) using a maximal voluntary power grip. Two orthogonal force measurements relative to the third metacarpal were resolved into a magnitude and corresponding angle. On average, magnitude increased 34.8 N as handle diameter increased from 2.54 cm to 3.81 cm, and then monotonically declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
125
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(137 citation statements)
references
References 18 publications
10
125
2
Order By: Relevance
“…Relative to what is known about how stone tool related behaviours may have influenced the evolution of human hand anatomy, however, a great deal less has been empirically demonstrated in respect to how biometric variation may have impacted on technological choices and cultural variability in the Lower Palaeolithic. The notion that individual biometric differences significantly influence hand-held tool use or gripping tasks is, however, both long lived and widely supported within engineering and ergonomic literature (e.g., Tichauer and Gage, 1977;Hall, 1997;Ruiz-Ruiz et al, 2002;Edgren et al, 2004;Nicolay and Walker, 2005;Hwang et al, 2011), with it having been demonstrated on a number of occasions that optimal tool forms are directly related to the biometric traits of tool users (e.g., Eksioglu, 2004;Seo and Armstrong, 2008). Such considerations indicate that those tool forms that are of greatest functional value, and thus the tool forms most likely to be replicated, are determined by the biometric conditions observed in a tool user's upper limb.…”
Section: Introductionmentioning
confidence: 99%
“…Relative to what is known about how stone tool related behaviours may have influenced the evolution of human hand anatomy, however, a great deal less has been empirically demonstrated in respect to how biometric variation may have impacted on technological choices and cultural variability in the Lower Palaeolithic. The notion that individual biometric differences significantly influence hand-held tool use or gripping tasks is, however, both long lived and widely supported within engineering and ergonomic literature (e.g., Tichauer and Gage, 1977;Hall, 1997;Ruiz-Ruiz et al, 2002;Edgren et al, 2004;Nicolay and Walker, 2005;Hwang et al, 2011), with it having been demonstrated on a number of occasions that optimal tool forms are directly related to the biometric traits of tool users (e.g., Eksioglu, 2004;Seo and Armstrong, 2008). Such considerations indicate that those tool forms that are of greatest functional value, and thus the tool forms most likely to be replicated, are determined by the biometric conditions observed in a tool user's upper limb.…”
Section: Introductionmentioning
confidence: 99%
“…The handle grip is improved by the optimum handle diameter in a way where it is easier to be secured in the hand and increases voluntary force applications. It is supported by other studies, where an optimal handle diameter increases the grip force and total normal force (Edgren et al, 2004;Kong and Lowe, 2005b;Mastalerz et al, 2009;Seo and Armstrong, 2008). At the same time, the secureness of the handle in the hand can be explained as the optimal handle diameter allowed the thumb and fingertips to work together against the palm, resulting in a greater reaction force (Seo and Armstrong, 2008).…”
Section: Effect Of Ergonomics Features On Handle Gripmentioning
confidence: 55%
“…The grip force increased with both torque directions, though the grip force for submaximal and maximal inward torques was respectively lower and higher than the grip force generated by outward torque. Besides that, the increase in handle friction (Seo et al, 2008a;2008b), increase in resistivity of handle shape towards finger phalanges segment (Kong et al, 2008) and an optimal(25-40mm) handle diameter (Edgren et al, 2004;Kong and Lowe, 2005a;Seo et al, 2007) also help in increasing the total normal force, resulting in a more stable and secure grip.…”
Section: The Effects Of Torque Directions On Grip Forcementioning
confidence: 99%
See 1 more Smart Citation
“…The patients were seated comfortably in a chair and were requested to grasp the dynamometer with maximum force. The grip test was performed in the standard arm position as recommended by the American Society of Hand Therapists; the shoulder adducted, elbow at 90 degrees fl exion, and forearm in neutral position (4). The patients were asked to squeeze the handle as hard as they could for 2 seconds.…”
Section: Methodsmentioning
confidence: 99%